IMPLEMENTASI PERILAKU CARING PERAWAT PELAKSANA TERHADAP KEPUASAN PASIEN DI RUANG RAWAT INAP RUMAH SAKIT GRANDMED LUBUK PAKAM - Rahmad Gurusinga; Tati Murni Karo-karo; Arfah May Syara; Syatriawati Suhaimi; Sari Desi Esta Ulina Sitepu; Anita Sri Gandaria Purba; Sarmana Sarmana (JURNAL PENGMAS KESTRA (JPK), 2021)
A hospital is said to be successful in providing health services if it is supported by several factors, one of which is quality nursing services. service quality. One form of nursing service that can be applied is the caring behavior of nurses because nurses are the people who interact with patients the most. This paper aims to provide the Implementation of Caring Behavior for Implementing Nurses on Patient Satisfaction in the Inpatient Room at Grandmed Lubuk Pakam Hospital. The method of implementing activities using questionnaires that are targeted in PKM activities are implementing nurses and inpatients. From the results of the activities carried out there was an increase in patient satisfaction up to 64.3%. With this PKM activity, it is hoped that it can improve the quality of health services at Grandmed Hospital and can further increase the satisfaction of visiting patients.